2023
DOI: 10.1021/cbmi.3c00033
|View full text |Cite
|
Sign up to set email alerts
|

The Application of Bio-orthogonality for In Vivo Animal Imaging

Abstract: The application of bio-orthogonality has greatly facilitated numerous aspects of biological studies in recent years. In particular, bioorthogonal chemistry has transformed biological research, including in vitro conjugate chemistry, target identification, and biomedical imaging. In this review, we highlighted examples of bio-orthogonal in vivo imaging published in recent years. We grouped the references into two major categories: bio-orthogonal chemistry-related imaging and in vivo imaging with bio-orthogonal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 92 publications
0
3
0
Order By: Relevance
“…Consequently, it was demonstrated that [ 68 Ga]­NOTA-SF-CV could be served as a feasible small-molecule PET tracer for sensitively and specifically monitoring cathepsin B activity in vivo . By combining the advantages of small-molecule probes and nanoprobes, the successful application of the tracer [ 68 Ga]­NOTA-SF-CV also demonstrated the applicability and universality of the SF scaffold designed by our group.…”
Section: Resultsmentioning
confidence: 99%
“…Consequently, it was demonstrated that [ 68 Ga]­NOTA-SF-CV could be served as a feasible small-molecule PET tracer for sensitively and specifically monitoring cathepsin B activity in vivo . By combining the advantages of small-molecule probes and nanoprobes, the successful application of the tracer [ 68 Ga]­NOTA-SF-CV also demonstrated the applicability and universality of the SF scaffold designed by our group.…”
Section: Resultsmentioning
confidence: 99%
“…The E-MISA strategy, due to its significant enhancement of functional nanoaggregate accumulation and retention in specific regions of interest, has prompted researchers to consider the potential utility of these accumulated nanoaggregates as “artificial receptors”. Leveraging these nanoaggregates combined with other functional molecules via bioorthogonal reactions, pretargeted imaging and/or theranostics in vivo can be achieved. Based on this idea and the concept, Rao’s group leveraged the optimized biocompatible intramolecular macrocyclization reaction between pyrimidinecarbonitrile and d -Cys with the inverse-electron-demand Diels–Alder (IEDDA) reaction between tetrazine (Tz) and trans -cyclooctene (TCO) and developed the E-MISA probe 32 for protease activity multimodality imaging in vivo in 2020 . Probe 32 (TCO-C-SNAT 4) contained a TCO handle for rapid reaction with Tz tags ( 33 and 34 ) via the IEDDA reaction, a casp-3/7-responsive DEVD substrate peptide, and a GSH reduction disulfide bond.…”
Section: E-misa Probes For Pretargeted Imaging and Theranostics Of Tu...mentioning
confidence: 99%
“…Chemical reactions compatible with biological systems have applications in chemical biology, biomedicine, imaging, diagnosis, and therapy. Among the many bioorthogonal reactions now available, the inverse electron demand Diels–Alder reaction of 1,2,4,5-tetrazines with strained dienophiles meets the strict criteria for use in living organisms, including humans . In recent years, researchers have made considerable efforts to fine-tune this bioorthogonal reaction for use in diverse applications. ,,, In addition to other promising synthetic methods, , cross-coupling reactions involving tetrazines provide many opportunities for modifying these heterodienes.…”
Section: Introductionmentioning
confidence: 99%